An intragenic deletion in the human PTPN6 gene affects transcriptional activity - Nehls, Michael; Schorpp-Kistner, Marina; Boehm, Thomas (Human genetics, 1995)
An intragenic deletion in the human PTPN6 gene is described. The PTPN6 gene maps to chromosome 12p12-13 and is shown to possess two alternative first exons. A 1.7-kb deletion occurring in the intron between the two alternatively used first exons is the result of an illegitimate recombination between two Alu-type repeats. The deletion increases the transcriptional activity of the distal promotor.